Comparative Genomics and Phylogenetics of Chloroplasts Reveal Lower Rates of Genetic Variation in Mango (Mangifera) - Chuanning Li; Jianfeng Huang; Zuan Wei; Yuzu Gao; Gulbar Yisilam; Enting Zheng; Fangfang Jiao; Zhenzhou Chu; Ying Su; Caihua Liao; Xuefen Lei; Jinyu Nong; et al. (Ecology and Evolution)
ABSTRACT The mango is an important economic crop with a long history of cultivation. However, studies on the characteristics among chloroplast (cp) genomes and the phylogenetic relationships of different mango varieties are still limited. To fill this research gap, we assembled, annotated, and compared the cp genomes of 23 mango germplasms. The mango cp genome exhibited a typical quadripartite structure, ranging in length from 157,604 to 158,949 bp. Each sequence encoded 129 genes, including 84 protein‐coding genes, 37 tRNA genes, and 8 rRNA genes. Nucleotide diversity analysis identified three mutation hotspot regions, trnH‐GUG‐psbA, ycf4‐cemA, and ndhF‐rpl32, which could be used to develop chloroplast‐specific markers. Phylogenetic analysis revealed that mango germplasm can be divided into four major clades, with wild and cultivated varieties forming independent clades. Interestingly, comparative chloroplast genomics and phylogenetics revealed a relatively low rate of genetic variation among cultivated mangoes. This phenomenon may be attributed to extensive interspecific hybridization and gene introgression events during mango domestication. This study provides valuable genomic resources for crop breeding and enhances our understanding of the genetic variation and phylogenetic relationships among different mango varieties.